2020
DOI: 10.1177/0021998320916528
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, hardness, and tribology properties of the (Cu/MoS2)/graphene nanocomposite via the electroless deposition and powder metallurgy technique

Abstract: To increase the strength and to reduce the wear rate of the copper composite that used as a solid self-lubricant materials, Cu/10MoS2/ (0, 0.2, 0.4, 0.6, 0.8, and 1 wt.% graphene nanosheets) hybrid matrix nanocomposites were fabricated using the electroless copper precipitation process followed by the cold pressing and sintering in a hydrogen atmosphere furnace with a double-heating rate cycle. The microstructure of the as-received powders, as well as the produced samples, was examined using the scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Before the GNs and SiC powders were put in the aluminum matrix, they were cleaned of manufacturing contamination by stirring in a 10 wt% sodium hydroxide solution and acetone for 1 h, respectively. To improve the adhesion between the Al and the ceramic particle reinforcements, a 3 wt% nano-silver metal was precipitated by the electroless plating process onto the GN and SiC particles' surface individually [48][49][50][51][52].…”
Section: Fabrication Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the GNs and SiC powders were put in the aluminum matrix, they were cleaned of manufacturing contamination by stirring in a 10 wt% sodium hydroxide solution and acetone for 1 h, respectively. To improve the adhesion between the Al and the ceramic particle reinforcements, a 3 wt% nano-silver metal was precipitated by the electroless plating process onto the GN and SiC particles' surface individually [48][49][50][51][52].…”
Section: Fabrication Proceduresmentioning
confidence: 99%
“…An essential phenomenon was also observed in which the wear rate increased as the sliding speed increased. As the sliding speed increased, the track of the sample on the frictional parts increased and, consequently, the wear rate increased [51].…”
Section: Wear Measurementsmentioning
confidence: 99%
“…The white grey area represents the Cu matrix, the grey area represents the Graphene nanosheets (GNSs) and the black ones are belonging to the pores. Generally, GNSs did not wet copper as the surface energy between them is high, so no good dispersion of the GNSs in the copper matrix takes place [13]. Addition of PCA and good milling parameters (milling time, ball to powder ratio and number of rotations rpm) are controllable to adjust the composite preparation.…”
Section: Microstructure Examinationmentioning
confidence: 99%
“…MoS 2 , a typical two-dimensional (2D) layered transition-metal dichalcogenide, has been widely used as a solid lubricant in the aviation field because of the excellent vacuum lubrication performance induced by its high interlayer anisotropy. However, MoS 2 tends to be oxidized by oxygen and water vapor in the atmospheric environment, which reduces the friction properties and shortens the wear life. , Research has shown that metal doping is a simple and economical method to improve the mechanical and tribological properties of MoS 2 solid lubricating materials. Meanwhile, the construction of micro-/nanotexture surfaces can not only improve the bearing capacity as power bearings but can also increase the storage capacity of lubricating materials and prolong the service life. On the other hand, the poor adhesion between MoS 2 and a matrix has always been a perplexing problem. Inspired by mussel adhesion proteins, polydopamine (PDA) formed by self-polymerization of dopamine is a polymer with outstanding adsorption performances, which can be adsorbed on various materials through strong covalent and non-covalent bonds to serve as an effective protective layer for nanostructures. In particular, the rich functional groups (e.g., −NH 2 , −OH and catechol groups) on the surface of PDA have strong chelating ability for transition-metal ions (e.g., Zn 2+ , Fe 3+ , and Mo 4+ ), which is beneficial to provide a reaction platform as a nucleation site to form a unique solid core–shell structure, thus improving the adhesion and load-bearing capacity of the film.…”
Section: Introductionmentioning
confidence: 99%